2019
DOI: 10.1111/1462-2920.14503
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of the obligate anaerobe Desulfuribacillus stibiiarsenatis MLFW‐2T to growth on antimonate and other terminal electron acceptors

Abstract: Summary Enzymes of the dimethyl sulfoxide reductase (DMSOR) family catalyse two‐electron redox reactions pivotal to the dissimilatory metabolism of a variety of organic and inorganic compounds. The draft genome of the obligately anaerobic bacterium Desulfuribacillus stibiiarsenatis MLFW‐2T contains 14 genes that are predicted to encode catalytic subunits of DMSOR family enzymes. We quantified transcription of these genes during growth on antimonate, arsenate, nitrate and selenate, with the goal of identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Metagenomic-binning retrieved bins associated with Geobacter and Pseudomonas , providing an opportunity to investigate the functional genes responsible for Sb­(V) reduction. Genes encoding for respiratory Sb­(V) reductase ( anrA ) were reported as the key gene for Sb­(V) reduction in Desulfuribacillus stibiiarsenatis MLFW-2T . In this study, anrA was only detected in bins associated with Geobacter .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Metagenomic-binning retrieved bins associated with Geobacter and Pseudomonas , providing an opportunity to investigate the functional genes responsible for Sb­(V) reduction. Genes encoding for respiratory Sb­(V) reductase ( anrA ) were reported as the key gene for Sb­(V) reduction in Desulfuribacillus stibiiarsenatis MLFW-2T . In this study, anrA was only detected in bins associated with Geobacter .…”
Section: Discussionmentioning
confidence: 70%
“…Given the chemical structural similarities between As and Sb, microorganisms may use similar metabolic pathways to transform both As and Sb. Indeed, the arrA gene encoding arsenate reductase could also contribute to the reduction of Sb­(V). , For example, Wang et al reported Sb­(V) reduction by Shewanella sp. ANA-3 through an arsenate respiratory reductase encoded by arrAB .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins present in bands of gels were identified as previously described [19]. [31] have been determined close to the Molybdo-enzymes of the sulfur metabolism, we added these clades to our study. Aio sequences, used as outgroup, had been sampled before [30].…”
Section: Protein Identification By Tandem Mass Spectrometrymentioning
confidence: 99%
“…The thermodynamics of the considered reactions is not sufficient to explain the selectivity of which the function is still unknown and the Anr family, described by Abin and coworkers from which the antimonate reductase function has been established and which is very closely related to the Mo-bisPGD enzymes involved in sulfur metabolism [31]. For each of the sequence subfamilies, we have also taken special care to include sequences from the most diverse phylogenetic origins.…”
Section: Phylogenymentioning
confidence: 99%